2001
DOI: 10.1557/proc-688-c5.9.1
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of a PZT thin Film Actuator for a Micro Electromechanical Switch Application

Abstract: Micromachined silicon cantilever beams actuated by the converse piezoelectric effect are of great interest for actuator applications, e.g. micro relays or micro mirrors. For the miniaturization and cost saving aspects the combination of silicon bulk micromachining and chemical solution deposition (CSD) technique for the ceramic thin films is very promising.This paper presents the results of such a fabrication process for a PbZr0.45Ti0.55O3 (PZT) thin film micro actuator for a switch application. The actuator w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…When an ac voltage V is applied to the PMN-PZT thin films, the piezoelectric coefficient d 31 is calculated as where is the tip deflection of the beam, L is the length of the beam, t is the layer thickness, and s is the mechanical compliance. 18,19) In this equation, ''1'' denotes the substrate and ''2'' denotes the piezoelectric thin film. We have already reported that the mechanical compliance of PZT thin films was smaller than that of PZT bulk ceramics.…”
Section: Piezoelectric Properties Of the Pmn-pzt Thin Filmsmentioning
confidence: 99%
“…When an ac voltage V is applied to the PMN-PZT thin films, the piezoelectric coefficient d 31 is calculated as where is the tip deflection of the beam, L is the length of the beam, t is the layer thickness, and s is the mechanical compliance. 18,19) In this equation, ''1'' denotes the substrate and ''2'' denotes the piezoelectric thin film. We have already reported that the mechanical compliance of PZT thin films was smaller than that of PZT bulk ceramics.…”
Section: Piezoelectric Properties Of the Pmn-pzt Thin Filmsmentioning
confidence: 99%
“…[1][2][3][4][5][6] Ferroelectric lead zirconate titanate (PZT) films are considered to be key material to realize the devices. However, the amount of the displacement and generative force of PZT thin films is not sufficient in some applications of microactuators.…”
Section: Introductionmentioning
confidence: 99%
“…1 Moreover, PZT thick films above 2 m in thickness have been investigated for use as optical waveguides 2 and in microelectromechanical system ͑MEMS͒ applications. 3 High-quality PZT films are essential in these applications and metallorganic chemical vapor deposition ͑MOCVD͒ is recognized as one of the most promising methods of deposition. This is because MOCVD-PZT films produce exceptional film quality together with good step conformability, a high deposition rate, and large areas of uniform film quality.…”
mentioning
confidence: 99%